Structural alterations in occipital cortices in trigeminal neuralgia: a voxel- and surface-based morphometric MRI study - Francesca Caramia; Antonio Di Renzo; Marco Fiorelli; Gianfranco De Stefano; Giulia Di Stefano; Maddalena Boccia; Maria Giulia Tullo; Gaia Cartocci; Costanza Gianni; Andrea Truini (The Journal of Headache and Pain)
Abstract Background To investigate gray matter structural alterations in patients with primary trigeminal neuralgia (TN) using voxel-based and surface-based morphometry, and to explore potential associations with clinical and neuroanatomical variables. Methods Thirty-eight patients with primary TN and twenty-six age-matched healthy controls underwent high-resolution 3 T MRI. Voxel-based morphometry (VBM) and surface-based morphometry (SBM) were conducted using CAT12. Neurovascular conflict (NVC) grade and trigeminal nerve atrophy were assessed from dedicated 3D-CISS and TOF-MRA sequences. Associations between morphometric alterations and clinical variables—including disease duration, pain phenotype and intensity, NVC grade, and nerve atrophy—were tested using linear regression models controlling for age and sex. Results VBM analysis revealed reduced gray matter volume in a bilateral cluster encompassing the cuneus and superior occipital gyrus (SOG) in TN patients compared to controls. SBM analysis identified lateralized cortical thinning in the left cuneus and right SOG, corresponding to the side of pain in left- and right-sided TN, respectively. No significant associations were observed between cortical alterations and clinical parameters. Morphometric differences were not found in classical pain-related regions such as the thalamus, insula, or anterior cingulate cortex. Conclusion Our findings reveal structural alterations in posterior regions, specifically the cuneus and superior occipital gyrus (SOG), in patients with TN. Although primarily visual, these regions are also implicated in multisensory integration and the affective dimension of chronic pain. Their alteration may reflect long-standing neuroplastic adaptations to persistent nociceptive input, rather than correlating directly with symptom severity.